Peningkatan Kinerja Pegawai melalui Penerapan Manajemen Talenta (Improving Employee Performance through the Application of Talent Management) - Luh Kartika Ningsih; Ni Nyoman Nathania Vighnasvari; AAN. Eddy Supriyadinata Gorda; Ni luh Putu Eka Yudi Prastiwi (STIE Malangkucecwara, 2026)
The purpose of this study was to examine the impact of talent management and human resource quality on employee performance at LPDs in Sawan District. The method used in this research is quantitative. The research data was collected through filling out 88 questionnaires distributed to respondents. In this study researchers used SmartPLS to analyze the data. The results prove that talent management has a positive and significant effect on employee performance. Talent management has a positive and significant effect on the quality of human resources. The quality of human resources has a positive and significant effect on employee performance. Talent management has a positive and significant effect on employee performance through the quality of human resources.